Short-Term High-Fat Diet Consumption Reduces Hypothalamic Expression of the Nicotinic Acetylcholine Receptor α7 Subunit (α7nAChR) and Affects the Anti-inflammatory Response in a Mouse Model of Sepsis - Souza, Anelise Cristina Parras; Souza, Camilla Mendes; Amaral, Camila Libardi; Lemes, Simone Ferreira; Santucci, Leticia Foglia; Milanski, Marciane; Torsoni, Adriana Souza; Torsoni, Marcio Alberto (Frontiers in Immunology, 2019)
Sepsis is one of the leading causes of death in hospitalized patients, and the chronic and low-grade inflammation observed in obesity is a major contributing factor. However, little is known with respect to a short-term high-fat diet (HFD) and its role in the development of sepsis. Here, we show for the first time, that short-term HFD consumption impairs early nicotinic acetylcholine receptor α7 subunit (α7nAChR)-mediated signaling, one of the major components of the cholinergic anti-inflammatory pathway, with a focus on hypothalamic inflammation and innate immune response. Mice were randomized to a HFD or standard chow (SC) for 3 days, and sepsis was subsequently induced by a lethal intraperitoneal (i.p.) injection of lipopolysaccharide (LPS) or by cecal ligation and puncture (CLP) surgery. In a separate experiment, both groups received LPS (i.p.) or LPS (i.p.) in conjunction with the selective α7nAChR agonist, PNU-282987 (i.p. or intracerebroventricular; i.c.v.), and were sacrificed 2 hours after the challenge. Short-term HFD consumption significantly reduced the α7nAChR mRNA and protein levels in the hypothalamus and liver. Immunofluorescence microscopy demonstrated lower cholinergic receptor nicotinic α7 subunit (CHRNA7)+ cells in the arcuate nucleus (ARC) and increased F4/80+ cells in the ARC and median eminence (ME), which can contribute to neuronal damage. Glial fibrillary acidic protein (GFAP)+ cells and neuronal nuclear antigen (NeuN)+ cells were also increased following consumption of a HFD. The HFD-fed mice died quickly after a lethal dose of LPS or following CLP surgery. LPS challenge raised cytokine levels in both groups; however, higher levels were observed in mice on a HFD. Moreover, PNU-282987 administration (i.p. or i.c.v.) reduced the levels of inflammatory markers in the hypothalamus following LPS injection; nevertheless, in HFD-fed mice, the effect of PNU-282987 was much less than that in mice fed standard chow. Here, we provide evidence that a short-term HFD impairs early α7nAChR expression in central and peripheral tissues, contributing to a higher probability of death in sepsis